2021
DOI: 10.1097/mao.0000000000003119
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Duct Length Calculation: Comparison Between Using Otoplan and Curved Multiplanar Reconstruction in Nonmalformed Cochlea

Abstract: Objective: To describe a new method to measure the cochlear parameters using Otoplan software, and to compare it with the traditional method using curved multiplanar reconstruction (cMPR). Study Design: Retrospective analysis using internal consistency reliability and paired sample t test. Setting: Tertiary referral center Patients: Thirty-four patients including 68 ears from a clinical trial were retrospectively reviewed. Main Outcome Measures: The length, width, height (distances A, B, H), and cochlear duct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Müller-Graff et al found a mean CDL of the organ of Corti (CDL OC ) of 34.55 mm ± 1.6 mm using the same Otoplan version 2.0 with multi-slice CT data of 20 subjects aged 64 ± 14.9 years [49]. Chen et al found a mean CDL of 34.37 ± 1.481 in 68 cochleae of 34 subjects with a mean age of 16.6 years (range: 0.6-63.6) without any statistical differences in age or side of the ear [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Müller-Graff et al found a mean CDL of the organ of Corti (CDL OC ) of 34.55 mm ± 1.6 mm using the same Otoplan version 2.0 with multi-slice CT data of 20 subjects aged 64 ± 14.9 years [49]. Chen et al found a mean CDL of 34.37 ± 1.481 in 68 cochleae of 34 subjects with a mean age of 16.6 years (range: 0.6-63.6) without any statistical differences in age or side of the ear [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact of different radiological diagnostic procedures, the fact that interindividual rater-related differences might also influence the selection of the optimal electrode array must also be taken into account when assessing the reliability of radiological measurement of the CDL. In previous studies, comparative evaluations of CDL measurements using Otoplan were mostly performed by two raters based on CT scans [32,36,37,55,56] and in one case based on an MRI scan [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OTOPLAN ® (CASCINATION AG, Bern, Switzerland, in corporation with MED-EL, Innsbruck, Austria) is the surgical planning software for otological procedures. The software has dedicated manual, semi-automatic, and automatic planning tools for application in general otology [ 29 ] and pre-operative surgical planning and reconstruction [ 30 , 31 , 32 , 33 , 34 , 35 ], as well as in post-operative image analysis [ 23 , 36 ] in hearing implant patients. For cochlear measurements specifically, the software requires a user to manually define the cochlear view and measure the cochlea’s diameter, width, and height, resulting in automatically calculated Cochlear Duct Length (CDL OC ) at the level of the Organ of Corti/Basilar membrane.…”
Section: Introductionmentioning
confidence: 99%